Fruit Consumption Patterns in The Community of Denpasar City - Ni Luh Made Santi Dewi; Gede Mekse Korri Arisena; Ni Wayan Putu Artini (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2022)
In general, fruit consumption in Bali Province shows a low level when compared to public consumption of other goods. Likewise with the City of Denpasar which is one of the areas with a fairly dense population so that the community's fruit consumption patterns are quite diverse. This study aims to determine and describe the pattern of fruit consumption in the community. The location of this research is Denpasar City. The sampling technique used is purposive and the sample used is housewives as many as 32 respondents. The data analysis technique used is descriptive analysis with data collection using observations, interviews, literature studies, and documentation. The research instrument used was a questionnaire. The results showed that the majority of people in Denpasar City (62.5%) consumed fruit as much as 150 grams/day in the sufficient category, and most (43.8%) people bought fruit/day for Rp 15.000,00/day. . There is a tendency that the greater the amount of income the respondent has, the more often the respondent buys fruit. The purpose of the people in Denpasar City to consume fruit is that most people (68.8%) use fruit for ordinary consumption/eaten and 31.3% for ceremonial facilities. The people's preference in Denpasar City in consuming fruit is that most people (81.3%) consume local fruit and 18.8% consume imported fruit.